Avaliação do revestimento a base de liga de níquel em aço estrutural, empregando o metal de adição ERNiCrMo-3 através da soldagem MIG/MAG - Magalhães, Sitonio Gomes de (2016)
The use of nickel alloy cladding components could be more frequently in petroleum industry. The crescent naphthenic corrosion and high molecular weight of national petroleum contribute for needs of materials with more resistance to corrosion, to temperature and to pressure. At this way, how part of systematic study, this work pretends to define operational range for adequate ERNiCrMo-3 weld overlay in structural steel with application of GMAW process, and to evaluate microstructural characteristics and mechanical properties in as welded and aging conditions. To realize the objective, were used an industrial robot, an electronic power source and an argon shielding gas for automated welding. To define the operational range, simple deposit welds and evaluation of superficial aspect, geometry and dilution were conducted. This step indicated that the welds in efficient current below 200 A showed high convexity and the variation of current for the calc of heat input is more significant for convexity and dilution of the weld than the variation of welding speed for the calc of same heat input. It was selected 290 A as welding current in two heat inputs (10 and 14 kJ/cm). The overlay at ASTM A 516 g60 steel was in simple layer, had overlap up to 40 pct between passes and had about 15 pct of dilution at the two heat inputs. The aging temperature employed was 600 oC for times of 100 and 300 hours. To metallurgical characterization was used: microhardness measures, optical microscope, scanning electron microscope, composition variations (EDAX), x-ray diffraction, electron backscatter diffraction and shear tests according ASTM A 265-03 standard specification. The microhardness and structures observed were, approximately, the same for the two heat inputs. Post aging HAZ showed absence of carbides. The dendritic structure had MC and Laves micro-phases in as welded condition and the aging provoked formation of secondary carbides, dissolution of primary carbides and formation of gama’’. As welded overlay microhardness was 240 HV and as welded HAZ was 190 HV. Aging HAZ was 120 HV and aging overlay was 290 HV for 100 h and 310 HV for 300 h. Only for aging conditions, were observed hard zones (800 HV) in interface of overlay, due to carbide concentration and aging of partially dilution zone, where the Fe favored the formation of gama’’. Despite the hardness differences of overlay, base metal and interface, were identified no cracks in metallographic analyses. The maximum shear strength was above of the specification requirement (140 MPa) in all conditions employed, the penetration shape (like finger) favored this result, and the aging provoked a gradual grow up in shear resistance.